Crucial Roles of Brassinosteroids in Cell Wall Composition and Structure Across Species: New Insights and Biotechnological Applications - Percio-Vargas, Francisco; Rubio-Valverde, Lourdes; Amorim-Silva, Vitor; Botella-Mesa, Miguel Ángel (Wiley, 2024)
Brassinosteroids (BR) are steroidal phytohormones essential for plant growth, development, and stress resistance. They fulfil this role partially by modulating cell wall structure and composition through the control of gene expression involved in primary and secondary cell wall biosynthesis and metabolism. This affects the deposition of cellulose, lignin, and other components, and modifies the inner architecture of the wall, allowing it to adapt to the developmental status and environmental conditions. This review focuses on the effects that BR exerts on the main components of the cell wall, cellulose, hemicellulose, pectin and lignin, in multiple and relevant plant species. We summarize the outcomes that result from modifying cell wall components by altering BR gene expression, applying exogenous BR and utilizing natural variability in BR content and describing new roles of BR in cell wall structure. Additionally, we discuss the potential use of BR to address pressing needs, such as increasing crop yield and quality, enhancing stress resistance and improving wood production through cell wall modulation.
Keywords: Biotecnología; Brassinosteroid; Cell wall; Development; Hormones; Salinity; Stress